2004
DOI: 10.1080/07315724.2004.10719386
|View full text |Cite
|
Sign up to set email alerts
|

Plasma D-Glucose, D-Fructose and Insulin Responses after Oral Administration of D-Glucose, D-Fructose and Sucrose to Normal Rats

Abstract: The intake of D-fructose, as the free hexose or as sucrose, favours D-glucose homeostasis. This is likely to be attributable to the reciprocal effects of the aldose and ketose upon their respective phosphorylation by glucokinase in both hepatocytes and insulin-producing pancreatic islet cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…The majority of ingested fructose passes via the portal circulation to the liver where it is rapidly cleared. Very little of this escapes the liver first-pass, limiting peak peripheral fructose levels to high micromolar or low millimolar concentrations [11, 16]. Intracellularly, fructose is rapidly phosphorylated by Ketohexokinase (KHK) into fructose 1-phosphate (F1P) (Figure 1).…”
Section: Biochemistry Of Fructose Metabolismmentioning
confidence: 99%
“…The majority of ingested fructose passes via the portal circulation to the liver where it is rapidly cleared. Very little of this escapes the liver first-pass, limiting peak peripheral fructose levels to high micromolar or low millimolar concentrations [11, 16]. Intracellularly, fructose is rapidly phosphorylated by Ketohexokinase (KHK) into fructose 1-phosphate (F1P) (Figure 1).…”
Section: Biochemistry Of Fructose Metabolismmentioning
confidence: 99%
“…From the physiological standpoint, a recent study revealed that both the immediate and delayed effects of D-fructose, as compared to D-glucose, upon secretory activity may differ in insulin-, somatostatinand glucagon-producing cells (10). The possible participation of D-fructose insulinotropic action in the improvement of Dglucose tolerance evoked in vivo by the ketohexose was also investigated (11). Last, in terms of the perturbation of islet function in type 2 diabetes, several studies aimed at comparing the fate of D-fructose in islets obtained from either control rats or animals currently used as models for this disease (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the fructose concentration in the peripheral blood after oral fructose administration have been examined in rats by using an enzymatic method [16] and in human subjects by using a colorimetric method [1721]. In the case of these methods, other reducing substances in the blood complicate the interpretation of the fructose analysis; for example, high glucose content interferes with the measurement of fructose concentrations.…”
Section: Discussionmentioning
confidence: 99%